A multicenter controlled trial on knowledge and attitude about cardiopulmonary resuscitation among secondary school children in Malaysia. - Rahman, Nik Hisamuddin Na; Keng Sheng, Chew; Kamauzaman, Tuan Hairulnizam T; Md Noh, Abu Yazid; Wahab, Shaik Farid A; Zaini, Ida Zarina; Fauzi, Mohd Hashairi; Ab Rahman, Andey; Dzulkifli, Nur Shahidah (2013)
BACKGROUND